Evaluasi Pembelajaran - Agisna, Robi; Jauhari, Zulfikri Alwi; Zuar, M. Saifudin; Sholihin, Muhammad; I, Anis Khusnul (Social Science Academic, 2023)
Implementation of learning in the classroom has consequences for a teacher to improve his role and competence, because a competent teacher will find it easier to manage classes and carry out evaluations for his students both individually and in class. Evaluation is an attempt to obtain information about student learning outcomes as a whole, both attitudes, knowledge, and skills. This can be used by teachers as a decision-making step in determining teaching and learning strategies. Thus, teachers need to conduct assessments in the process and student learning outcomes. So that this paper will examine the evaluation of learning related to the achievement of student learning competencies, as well as innovations in improving learning evaluation in accordance with the times. This research uses descriptive qualitative research. This type of research library research with the method of literature study.